PERAN GURU DAN BUDAYA SEKOLAH DALAM MENINGKATKAN KARAKTER ANAK USIA DINI - Maria Faustina Eno Rato; Efrida Ita; Maria Fransiska Tolo; Maria Yohana Melina Mi; Emirensiana Lago (STKIP Subang, 2026)
This article aims to describe the role of teachers and school culture in developing the character of early childhood at Caritas Maukeli Kindergarten. This study used a qualitative descriptive approach with observation, interviews, and documentation techniques. The results show that teachers act as role models through exemplary behavior, habituation, and meaningful learning activities. A positive school culture also supports the development of children's character, such as discipline, honesty, and responsibility. Therefore, good teachers and school culture play a crucial role in creating effective character education for early childhood